The Influence of Transformational Leadership Style, Interpersonal Communication, and Motivation on Employee Performance - Enda, Nura; Parashakti, Ryani Dhyan (Lentera Ilmu Nusantara, 2025)
This study aims to analyze the influence of Transformational Leadership style, interpersonal communication, and work motivation on employee performance at PT. Artomoro Gemilang Teknik. An effective leadership style is believed to create good interpersonal communication patterns and enhance employee work motivation. Strong interpersonal communication enables clear information flow and strengthens relationships among team members, thus reducing the potential for miscommunication. Work motivation also plays a crucial role in maintaining work spirit and employee commitment to the company's goals. The research results are expected to provide practical recommendations for the company in implementing an appropriate leadership style, improving interpersonal communication, and designing effective work motivation strategies to maximize employee performance. This study uses a Likert scale questionnaire for data collection and quantitative analysis to test the influence of each variable on employee performance, utilizing SPSS version 25 with 30 respondents.